2021
DOI: 10.3389/fcimb.2021.639177
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blockers (ARBs Antihypertensive Agents) Increase Replication of SARS-CoV-2 in Vero E6 Cells

Abstract: Several comorbidities, including hypertension, have been associated with an increased risk of developing severe disease during SARS-CoV-2 infection. Angiotensin II receptor blockers (ARBs) are currently some of the most widely-used drugs to control blood pressure by acting on the angiotensin II type 1 receptor (AT1R). ARBs have been reported to trigger the modulation of the angiotensin I converting enzyme 2 (ACE2), the receptor used by the virus to penetrate susceptible cells, raising concern that such treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Regarding RAS blockade and ACE2 expression we found that smokers under RAS blockade exhibited a slightly enhanced amount of ACE2-expressing type II pneumocytes compared to never smokers. Supporting our results, recently it has been shown that ARBs increased SARS-CoV-2 replication in Vero E6 cells that correlated with the ARBs-induced up-regulation of ACE2 expression [45] . In contrast, in a study by Lee et al [8] using a small sample size of patients taking ACEIs, upper respiratory tract ciliary ACE2 expression was slightly decreased compared to matched controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding RAS blockade and ACE2 expression we found that smokers under RAS blockade exhibited a slightly enhanced amount of ACE2-expressing type II pneumocytes compared to never smokers. Supporting our results, recently it has been shown that ARBs increased SARS-CoV-2 replication in Vero E6 cells that correlated with the ARBs-induced up-regulation of ACE2 expression [45] . In contrast, in a study by Lee et al [8] using a small sample size of patients taking ACEIs, upper respiratory tract ciliary ACE2 expression was slightly decreased compared to matched controls.…”
Section: Discussionsupporting
confidence: 91%
“…We found that older smokers and former smokers comprised the largest percentage of subjects exhibiting higher ACE2 protein content. In agreement, higher ACE2 expression in smokers compared to never smokers have been reported [17] , [43] , [44] , [45] . In contrast, other reports have shown that current smokers and never smokers have similar levels of bronchial epithelial cell mRNA ACE2 [46] and ACE2 protein in both bronchial and alveolar epithelial cells [47] as well as nasal ciliary cells [9] .…”
Section: Discussionsupporting
confidence: 82%
“…As its name suggests, this type of medication works by blocking the Ang II receptor, given its role in promoting the constriction of blood vessels and in increasing blood pressure [ 113 , 114 ]. Since these receptors are found in the heart, blood vessels, kidneys, and intestine [ 115 , 116 ], blocking their action helps in lowering blood pressure and preventing kidney and heart damage [ 117 ]. In addition, blocking AT1R may reduce acute lung injury and the response of inflammatory mediators [ 62 ].…”
Section: At1r Blockers (Arbs): a Potential Treatment Strategy In Covi...mentioning
confidence: 99%
“…Azilsartan, eprosartan, irbesartan, and telmisartan induced a higher expression of ACE2 in Vero E6 cells than in untreated cells, which also have increased expression of AT1R, the binding of which to these blocking molecules was reduced. Interestingly, there are significant differences in the ability of ARBs to induce the overexpression of ACE2 once bound to AT1R, since some drugs at 7 µM (e.g., telmisartan) led to higher ACE2 increase than others when used at higher concentration (e.g., irbesartan at 60 µM) [ 117 ]. It is also known that following Ang II binding, AT1R triggers ACE2 cleavage and shedding, dependent on the p38–MAPK pathway, resulting in reduced cell surface expression [ 136 , 137 ].…”
Section: At1r Blockers (Arbs): a Potential Treatment Strategy In Covi...mentioning
confidence: 99%
See 1 more Smart Citation